Popliteal artery aneurysm rupture with pseudoaneurysm formation: Case report (Research, Society and Development, 2022)
A popliteal artery aneurysm is a rare rupture. The article aims to describe the case of a patient who developed complications from a popliteal artery aneurysm. The case report addresses the treatment of a 78-year-old patient who started a picture of pain and pulsatile mass in the right popliteal hollow region. The clinical picture started seven days after the left suprapatellar amputation due to embolic complications of a left popliteal artery aneurysm. Ultrasonography with Doppler and angiotomography were performed, confirming the diagnosis of aneurysm rupture of the aneurysm of the right popliteal artery with pseudoaneurysm formation. The patient underwent limb revascularization with exclusion of the ruptured aneurysm and had a good evolution in the immediate postoperative period.